2004
DOI: 10.1191/0961203304lu485oa
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of anti-dsDNA antibody isotypes: IgG/IgM ratio of anti-dsDNA antibodies as a prognostic marker for lupus nephritis

Abstract: The objective of this paper is to investigate the association between patterns of anti-dsDNA antibody isotypes and specific clinical manifestations (categorized in renal, musculoskeletal, cutaneous, hematological, pulmonary, neurological and cardiac). Sera of 202 systemic lupus erythematosus (SLE) patients, 33 patients suffering from other autoimmune diseases and 115 healthy blood donors were analysed for anti-dsDNA antibodies by IgG-, IgA- and IgM-specific ELISA, Farr-assay and CLIF. A subset of 24 SLE patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
94
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 25 publications
12
94
0
3
Order By: Relevance
“…In a recent study, absence of lupus nephritis was suggested to be a consequence of a predominance of the IgM isotype of anti-dsDNA antibodies (25). SLE patients with a permanent ratio of IgG to IgM of Ͻ0.8 did not develop lupus nephritis, despite high levels of antidsDNA antibodies.…”
Section: Protective Antibodies In Autoimmune Diseasesmentioning
confidence: 99%
“…In a recent study, absence of lupus nephritis was suggested to be a consequence of a predominance of the IgM isotype of anti-dsDNA antibodies (25). SLE patients with a permanent ratio of IgG to IgM of Ͻ0.8 did not develop lupus nephritis, despite high levels of antidsDNA antibodies.…”
Section: Protective Antibodies In Autoimmune Diseasesmentioning
confidence: 99%
“…Anti-double-stranded DNA (anti-dsDNA) antibodies are recognized as highly specific diagnostic markers for SLE, are found in 60 -80% of patients (1)(2)(3), and have been included in the American College of Rheumatology (ACR) classification criteria since 1982 (4,5). Anti-dsDNA antibodies have been observed to be strongly correlated with SLE for more than 50 years.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, Prasad et al found that the presence of anti-dsDNA antibodies as measured at 2 consecutive visits was not predictive of damage at 5 years (43), which is certainly consistent with our findings in SACQ patients. The relative pathogenicity of anti-dsDNA antibody isotypes is now appreciated, with anti-dsDNA IgG, specifically IgG2 and IgG3, found to be most pathogenic, perhaps owing to a propensity to activate complement or engage Fc receptors (1,2,30,44,45). We believe a particular strength of this study lies in the use of the Farr assay to detect anti-dsDNA antibodies, as it has been found to preferentially bind high-avidity antibodies and to be best correlated with global disease activity, as well as renal and vasculitic involvement (1,46).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of these auto-antibodies varies and may be associated with individual manifestations of SLE. For instance, antibody to dsDNA antibodies which is present in 30%-70% of the serology of SLE patients correlates with the development and progression of glomerulonephritis [11] whereas antibody to Ro is associated with photosensitivity [12].…”
Section: Roles Of B Cells In Slementioning
confidence: 99%